IMPLEMENTATION OF SLAMET RIYADI VALUE IN FORMING QUALIFIED STUDENTS TO FACE THE INDUSTRIAL REVOLUTION 4.0 - Sukma Evi Romadhoni (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
Ignatius Slamet Riyadi is one of the young figures who have a high nationalism spirit since childhood. Lots of revolutionary actions carried out by Ignatius Slamet Riyadi in his efforts to fight for Indonesian independence. Slamet Riyadi is a figure who is very active in several military operations. He is not only a professional on duty but also someone who cares about the people and welfare in society. He collaborated with the people to jointly fight for independence until finally Slamet Riyadi died in the military operation and was buried in Ambon. The values contained in Slamet Riyadi are in line with the needs of human resources in order to face the era of the industrial revolution 4.0. In order to realize Industry 4.0 in Indonesia, academics are required to be involved in developing research and preparing adequate human resources. This article aims to examine the aspects and direction of the development of research and preparation of human resources at the University of Slamet Riyadi Surakarta, an institution established in order to play an active role in the development of science and technology for sustainable human welfare, upholding cultural values and the spirit of Pancasila taken from the Revolutionary Heroes Ignatius Slamet Riyadi. This article is expected to give an idea of what Industry 4.0 is and the efforts made by Slamet Riyadi University in implementing Slamet Riyadi's values to face the fourth industrial revolution. Keywoards : slamet riyadi, industry 4.0, academics, values